Antibacterial activity of Actinomycetes symbiont with seaweeds: a prosperous agent of animal antibacterial - Bertoka Fajar Surya Perwira Negara; Riyanti Riyanti; Bintang Marheani; Aradea B. Kusuma (Syiah Kuala University, 2016)
Circulation of synthetic antibacterial chemicals which is used continuously can cause resistance to bacteria. Alternative synthetic antibiotics research then comes up as an urgent need. Recently, the discovery of new antibacterial agents is looking for Actinomycetes. Actinomycetes are one of the active marine bacteria which produce secondary metabolites that could be used as antibacterial. The objective of this study was to evaluate the antibacterial activities of Actinomycetes symbiont with Halimeda macroloba, Gelidiella acerosa, and Turbinaria ornata in Pangandaran beach, Indonesia. A total of 41 Actinomycetes were isolated from 3 species of seaweed. Rep PCR amplification method was used to characterize and identify the relationship between samples. Primer BOX A1R (5’- CTACGGCAAGGCGACGCTGACGCTGACG-3’), 27F (5'-AGTTTGATCMTGGCTCAG-3') and 1492R (5'- TACGGYTACCTTGTTACGACTT-3') was used in amplification 16s DNA. Six isolates from the representative cluster dendogram were selected for secondary metabolites extraction using ethyl acetate solvent, meanwhile agar diffusion method was used as Antibacterial activity assay using E. coli, Proteus sp., and Enterobacter sp. as the bacterial test. The results showed that the activity of secondary metabolite extracts of Actinomycetes symbiont with Halimeda macroloba presented the highest inhibition zone on 3 bacterial tests. In the future, it could be a potential antibacterial agent against animal pathogenic bacteria.